Effect of investment on financial and sports results - Mijatovic, Predrag; Pavlović, Vladan; Milačić, Ljubiša (Industrija, 2015)
This study investigated the correlation between investment, financial results and sport results achieved and to evaluate the relative efficiency of Serbian football clubs. In this regard, two postulations were examined: firstly, investments in football clubs produce better sports results; secondly, investments in football clubs result in a stronger financial position. A correlation analysis and Data Envelopment Analysis (CCR model) were applied. Thirteen football clubs were included in the analysis, which represents eighty per cent of the Serbian Football League First Division Clubs. The study was conducted in the period 2009–2011that includes football seasons 2009-2010, 2010-2011 and 2011-2012. A strong positive correlation between investment and sport results was found only for the top football clubs, while the econometric regression did not show any correlation. The findings also show that there is no relation between investment and net income. The analysis of technical efficiency confirmed these findings, which revealed that the best football clubs are usually the farthest away from the efficiency frontier.
Keywords: Investment; Football; Correlation; Analysis